Habitat Preference and Suitability Habitat of Cuscus at PT Wijaya Sentosa, Teluk Wondama Regency - Firman Arief; Nyoto Santoso; Dede Aulia Rahman (Institut Pertanian Bogor (IPB University), 2022)
Previous studies are most focusing on the species identification and habitat used by cuscus, while habitat changes are the most threats on cuscus. Habitat changes caused by the operation of logging concession such as PT Wijaya Sentosa creates an impact to the habitat selection of cuscus, which is highly dependent on forest cover. Efforts to protect cuscus species in production forests need to be carried out to ensure their sustainability habitat. This study aims to determine habitat preference of cuscus and model the suitability habitat of cuscus. The Neu index calculation is used to measure the level of habitat preference, while the habitat sustainability map is modelled by biotic, abiotic, and human disturbance components into MaxEnt application. Vegetation data is analyzed to describe tree density, tree richness, and strata using of cuscus by SexFI application. The study showed that the most preferred habitat by cuscus is LoA 2018 because LoA 2018 had the most species richness so cuscus might be able to choose their vegetation food. The habitat suitability of cuscus in PT Wijaya Sentosa covers 21,116.59 ha and didn't follow the pattern of increasing Et+ logging but was strongly influenced by logged blocks as much as 55.2% contribution.